Understanding the Role of Love Language in Interpersonal Communication within Same-Gender Friendships - Dinda Apriliani Putri; Ummu Salamah; Zikri Fachrul Nurhadi (Universitas Tribhuwana Tungga Dewi, 2025)
Interpersonal communication is a critical element in building and maintaining the quality of same-gender friendships, particularly among university students. These friendships are often misunderstood, with assumptions that they are linked to sexual orientation. This study examines the role of love language in interpersonal communication through five key dimensions: openness, empathy, supportive behavior, positive attitude, and equality, and how these dimensions influence same-gender friendships. A qualitative approach was used, involving in-depth interviews with four pairs of informants at Garut University, all students aged 18-25 who have been friends for at least two years. Data validity was ensured through source and method triangulation, with input from experts in communication and psychology to enrich the analysis. The results show that the dimensions of openness, empathy, supportiveness, positivity, and equality are fundamental in fostering emotional connections and improving the overall quality of friendships. These dimensions contribute to stronger bonds of trust, empathy, and mutual support, which are essential for maintaining harmonious and meaningful relationships. The study concludes that effective and honest communication, especially empathy and openness, is key to sustaining healthy same-gender friendships. It also encourages further research into the role of communication in diverse social relationships and highlights the importance of continually developing communication skills to nurture and strengthen interpersonal relationships.Komunikasi interpersonal merupakan elemen penting dalam membangun dan mempertahankan kualitas persahabatan sesama jenis, khususnya di kalangan mahasiswa. Persahabatan ini sering kali disalahpahami, dengan anggapan bahwa hal tersebut berkaitan dengan orientasi seksual. Penelitian ini menganalisis peran bahasa cinta dalam komunikasi interpersonal melalui lima dimensi utama: keterbukaan, empati, perilaku mendukung, sikap positif, dan kesetaraan, serta bagaimana dimensi-dimensi ini mempengaruhi persahabatan sesama jenis. Pendekatan kualitatif digunakan, dengan melakukan wawancara mendalam dengan empat pasangan informan di Universitas Garut, yang semuanya merupakan mahasiswa berusia 18-25 tahun yang telah berteman selama minimal dua tahun. Validitas data melalui triangulasi sumber dan metode, dengan masukan dari para ahli komunikasi dan psikologi untuk memperkaya analisis. Hasil penelitian menunjukkan bahwa dimensi keterbukaan, empati, dukungan, sikap positif, dan kesetaraan sangat penting dalam memperkuat hubungan emosional dan meningkatkan kualitas persahabatan. Dimensi-dimensi ini berkontribusi pada ikatan kepercayaan, empati, dan saling mendukung, yang esensial untuk mempertahankan hubungan yang harmonis dan bermakna. Penelitian ini menyimpulkan bahwa komunikasi yang jujur dan empatik, terutama keterbukaan dan empati, adalah kunci untuk mempertahankan persahabatan sesama jenis yang sehat. Penelitian ini juga mendorong eksplorasi lebih lanjut mengenai peran komunikasi dalam berbagai konteks hubungan sosial dan menekankan pentingnya pengembangan keterampilan komunikasi yang terus-menerus untuk memperkuat hubungan interpersonal.